Simultaneous Allocation Renewable DGs and Capacitor for Typical Indian Rural Distribution Network using Cuckoo Search Algorithm - P, Balamurugan; Yuvaraj, T; P, Muthukannan (International Journal of Engineering and Technology, 2018)
Nowadays, simultaneous allocation of renewable distributed generations (REDGs) along with shunt capacitors (SCs) in RDS distribution networks is getting more attention by the researchers. Since it mitigates the system losses, enhance the bus voltages, power factor improvement, power quality enhancement and reduces the environmental threats. In the proposed work an advanced approach is implemented for simultaneous allocation REDGs and SC for Indian 28- rural bus network. For decrease the losses and maximize the system stability  is the  main objective of thispaper. The locations and sizing of theses REDGs and SCs have been determined with help of cuckoo search algorithm (CSA).